Cytotoxic and Optically Active Pyrisulfoxins From the Endophytic Streptomyces albolongus EA12432 - Du, Yuqi; Wang, Chen; Cui, Guodong; Chu, Yiwen; Jia, Qian; Wang, Yi; Zhu, Weiming (Frontiers in Chemistry, 2020)
R(–)-Pyrisulfoxin C (1), S(+)-pyrisulfoxin D ((+)-2), R(–)-pyrisulfoxin D ((–)-2), pyrisulfoxin E (13), S(+)-pyrisulfoxin F ((+)-14), and R(–)-pyrisulfoxin F ((–)-14), six new caerulomycin derivatives with a 2,2'-bipyridine skeleton, were obtained from the cultures of the endophytic Streptomyces albolongus EA12432 with Aconitum carmichaeli (Ranunculaceae). Additionally, the racemic pyrisulfoxins A ((±)-3) and B ((±)-4) were resolved into optically pure compounds and identified the configurations for the first time. The racemic pyrisulfoxin D ((±)-2) displayed significant cytotoxicity against a series of cancer cell lines with IC50 values ranging from 0.92 to 9.71 μM. Compounds 7, 8 and (±)-3 showed cytotoxicity against the HCT-116, HT-29, BXPC-3, P6C and MCF-7 cell lines. Notably, compounds 7 and 8 have a strong inhibition both on the proliferation of human colon cancer cells HCT-116 and HT-29 with IC50 values ranging from 0.048 to 0.2 μM (doxorubicin, 0.21 and 0.16 μM), and compound 1 showed a selective inhibition on the proliferation of the gastric carcinoma cell lines, N87, with an IC50 value of 8.09 μM. Optically pure compounds R(–)-14 and S(+)-14 showed weak cytotoxicity against HCT-116 and MCF-7 cell lines with IC50 of 14.7 μM and 10.4 μM, respectively. Interestingly, the active compounds 1 and (±)-2 were no inhibition on the two human normal cell lines, HEK-293F and L02 (IC50 >100 μM).